Decrypting China’s Quantum Leap. - Sharma, Munish (China Journal, 2018)
China has achieved major scientific accomplishments since embarking in 2001 on a journey to harness the vast potential of quantum mechanics in information security and military applications. Chinese scientists claimed success in satellite-based entanglement distribution in June 2017. Three months later, in September 2017, the 2,000-kilometer Quantum Communication Line between Shanghai and Beijing opened the world’s first trunk line of secure quantum telecommunications. China’s political leadership has demonstrated its interest and support in this very expensive endeavor, owing to the strategic and military applications of quantum cryptography, quantum computing, and quantum metrology for highly secure communications, stealth submarine operations, and military code breaking. This article explores the rapid development and evolution of research in quantum communications in China, the critical role of political leadership, and the immense opportunities it holds in the military domain.